EFEKTIVITAS MODEL DISCOVERY LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII - Ella Dania Sari; Sri Yunita Ningsih (Ensiklopedia Education Review, 2026)
This study examines the effectiveness of the Discovery Learning model in enhancing mathematical concept comprehension among seventh-grade students at SMP Negeri 2 Lirik. Mathematical concept comprehension constitutes a fundamental capability that learners must develop, as it enables them to understand, interpret, and apply mathematical principles correctly during problem-solving activities. Nevertheless, a significant number of students continue to face challenges in grasping mathematical concepts, largely because classroom instruction remains predominantly teacher-directed. A qualitative descriptive methodology was adopted for this investigation. Participants were drawn from the seventh-grade cohort at SMP Negeri 2 Lirik, with data gathered through classroom observation, in-depth interviews, and document review. The analytical framework employed was the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion formulation. Trustworthiness of the data was established through source triangulation and methodological triangulation. Findings revealed that the adoption of Discovery Learning substantially improved students’ conceptual understanding of mathematics. Learners demonstrated heightened participation throughout sessions, greater confidence in articulating their reasoning, and an improved capacity to express mathematical ideas in their own words. Moreover, students showed notable advancement in tackling mathematical problems and transferring concepts across different contexts. Discovery Learning also fostered a more interactive and engaging classroom environment, as students took an active role in constructing their own understanding. The study concludes that Discovery Learning is an effective instructional approach for deepening mathematical concept comprehension among seventh-grade learners and may serve as a viable alternative to conventional teaching methods.Keywords: discovery learning; mathematical conceptual understanding; mathematics learning; junior high school; qualitative research